MICROPLASTIC IN THE DEEP-SEA SEDIMENT OF SOUTHWESTERN SUMATRAN WATERS - Cordova, Muhammad Reza; Wahyudi, Aan J. (Marine Research in Indonesia, 2016)
Indonesia was recently ranked second on the list of countries producing plastic waste. Plastic can be degraded by thermal oxidation either with ultraviolet radiation and by mechanical to a very small size the size will be smaller. Degraded plastic with small sizes (<5 mm) measured has been micrometers known as microplastic. We took sediment samples on 07-18 May 2015 in EWIN 2015 cruise, which part of the contribution of Indonesian researchers for the International Indian Ocean Expedition-2 program, at 66.8 to 2182 m below sea level. Microplastic analysis from the sediment was carried out by using flotation methods. We found microplastic in 8 locations out of 10 sampling locations. We found 41 particles microplastic with a form of granules (35 particles) and fibers (6 particles). Most of microplastic particles were found at depths less than 500 m with 20 particles. The discovery of microplastic in the sediment from the sea of western Sumatra at a depth more than 2000 m, indicated that plastic, considered new developed materials (early nineteen centuries made), has invaded marine areas, including pristine areas. It confirms the statement that plastic waste has spread widely to different areas of the seas and oceans, including remote and mostly unknown areas such as the deep sea.